Cultural representation and Chinese gardens abroad: an exploratory study of Dunedin Chinese Garden, New Zealand - Cui, Jing (Auckland University of Technology, 2013)
The western passion for Chinese culture, especially Chinese garden culture, began in the late 17th century. Today Chinese gardens abroad are often features of tourism destinations. This research is a case study of the Dunedin Chinese Garden which is a recent example in New Zealand. This dissertation reports on findings of the research using interviews conducted with key stakeholders involved in the development of the Dunedin Chinese Garden, and outlines its history, the development background, the management and marketing approach, current visitation and key stakeholders’ views of the Garden. Particular focus has been given to exploring the Dunedin Chinese Garden’s many potential but quite different roles in Dunedin’s development. These include: commodifiable resource for tourism products and services, catalyst in local area regeneration and revitalization, enhancer of environmental amenity and contributor to place image or brand. The findings, informed by relevant literature, are discussed to highlight the Garden’s subtle meanings in representing Chinese culture, Chinese diasporic culture and sister-city relationship with Shanghai. Conclusions relate to the rationale for the current development, tourism performance and markets, the challenges faced in interpreting and promoting of the Dunedin Chinese Garden in New Zealand. Finally, suggestions are made regarding how the Dunedin Chinese Garden could possibly be best developed and attract visitors.
Keywords: Chinese gardens abroad; Cultural representation; Sister city relationship; Chinese immigrant in New Zealand; The Dunedin Chinese Garden; Cultural heritage and authenticity